2018
DOI: 10.12659/msm.909649
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Nomogram for Disease-Specific Survival in Patients with Pancreatic Ductal Adenocarcinoma of the Head of the Pancreas Following Pancreaticoduodenectomy

Abstract: BackgroundThis study developed and validated a nomogram to predict patient prognosis for pancreatic ductal adenocarcinoma (PDAC) of the head of the pancreas following pancreaticoduodenectomy.Material/MethodsRetrospective data were obtained from 4,383 patients with PDAC of the head of the pancreas who underwent pancreaticoduodenectomy between 2004–2013 from 11 Registries Research Data of the Surveillance, Epidemiology,and End Results (SEER) database. Cox proportional hazards model was used to identify independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
(19 reference statements)
2
24
0
Order By: Relevance
“…It only incorporates some features of the tumors into the staging system, and the prognostic factors are far more than these. Previous studies have found that age, sex, grade, different treatment and even marital status are important independent factors affecting the prognosis of patients with PC (Li, Zhou & Zhao, 2018;He et al, 2018;Wang et al, 2016;Baine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It only incorporates some features of the tumors into the staging system, and the prognostic factors are far more than these. Previous studies have found that age, sex, grade, different treatment and even marital status are important independent factors affecting the prognosis of patients with PC (Li, Zhou & Zhao, 2018;He et al, 2018;Wang et al, 2016;Baine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies have shown inconsistent results depending on the research institute and the study cohort, and the predictors have not been able to directly contribute to improving prognosis because most of them are unmodifiable factors [3,11,12]. To complement the inconsistency of the prognostic factors of PDAC and to more accurately predict the survival possibility, predictive nomograms developed by analysing the contribution of each factor have been reported [13][14][15][16]. Although these outcomes may contribute to predicting the overall outcomes of a patient, there are still limitations in contributing to prognosis improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A particular case report in which a patient with ITPN and no metastases underwent pylorus-preserving duodenopancreatectomy showed survival at five months post-surgery with no evidence of remaining disease [ 9 ]. However, the prognosis of ITPN is favorable in comparison to the more commonly encountered pancreatic ductal adenocarcinomas, where median disease-specific survival was 17.0 months in a dataset of 4383 patients [ 10 ]. The patient continues to survive 14 months after diagnosis, and 11 months following pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%